2022
DOI: 10.3390/ijms231911177
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Glucose Levels Are Associated with Xanthine Oxidase Activity in Overweight Type 2 Diabetic Women

Abstract: Oxidative stress plays an important role in vascular complications observed in patients with obesity and Type 2 Diabetes (T2D). Xanthine oxidase (XO) breaks down purine nucleotides into uric acid and contributes to the production of reactive oxygen species (ROS). However, the relationship between XO activity and glucose homeostasis in T2D subjects with obesity is unclear. We hypothesized that disordered glucose levels are associated with serum XO activity in overweight women and men with T2D and without hyperu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…However, none of these genera was found to associate with xanthine in human plasma in the GutsyAtlas data [ 32 ]. The reduced xanthine concentrations upon HFD exposure are more in line with reports of increased activity of the purine catabolism enzymes xanthine oxidoreductase and xanthine oxidase in serum of individuals with obesity, metabolic syndrome and T2D [ 33 , 34 , 35 ]. In our study, pathway analysis indicated altered purine metabolism at both 1 and 8 weeks of HFD exposure in mice, and also in individuals with T2D.…”
Section: Discussionsupporting
confidence: 86%
“…However, none of these genera was found to associate with xanthine in human plasma in the GutsyAtlas data [ 32 ]. The reduced xanthine concentrations upon HFD exposure are more in line with reports of increased activity of the purine catabolism enzymes xanthine oxidoreductase and xanthine oxidase in serum of individuals with obesity, metabolic syndrome and T2D [ 33 , 34 , 35 ]. In our study, pathway analysis indicated altered purine metabolism at both 1 and 8 weeks of HFD exposure in mice, and also in individuals with T2D.…”
Section: Discussionsupporting
confidence: 86%
“…T2DM leads to excessive ROS production through various pathways. Early research suggested that glucose could directly stimulate excessive ROS production ( Du et al, 1999 ), but later studies found that high glucose (HG) activates various enzymatic cascades in mitochondria ( Rizwan et al, 2020 ), including the activation of NADPH oxidase ( Jansen et al, 2013 ), NO synthase uncoupling ( Sasaki et al, 2008 ), and the stimulation of xanthine oxidase ( Hernandez-Hernandez et al, 2022 ). Similarly, elderly individuals often have comorbidities such as dyslipidemia and hypertension, which can also induce ROS production.…”
Section: The Pathological Mechanisms In Elderly Diabetes Mellitusmentioning
confidence: 99%
“…Thus, further revealing the flexibility of the complex and possible XO inhibition. Additionally, high XO activity was reported to be associated with type 2 diabetes [60]. Therefore, a decrease in its activity might be associated with antidiabetic activity via alleviation of oxidative stress.…”
Section: Antioxidant Activitymentioning
confidence: 99%